Determinan Kinerja Guru: Kompensasi dan Lingkungan Kerja - Sholehati, Putri; Hadijah, Hady Siti (Universitas Pendidikan Indonesia, 2019)
The study was conducted to determine the description of compensation, work environment, and performance of honorary teachers, and to determine the effect of compensation and the work environment on the performance of honorary teachers at the Cirebon Islamic Center SMK. The research method used is a quantitative method with a survey method. The theory used is the theory of organizational behavior from Stephen P Robbins. The data collection tool is a questionnaire given to respondents of 40 honorary teachers. The data analysis technique uses multiple regression analysis. The results of the study show that (1) the description of high compensation (2) a description of the conducive work environment (3) an overview of the performance of moderate honorary teachers (4) there is an effect of compensation and work environment on the performance of honorary teachers both partially and simultaneously.ABSTRAKPenelitian dilakukan untuk mengetahui gambaran tentang kompensasi, lingkungan kerja, dan kinerja guru honorer, serta untuk mengetahui pengaruh kompensasi dan lingkungan kerja terhadap kinerja guru honorer di SMK Islamic Centre Kabupaten Cirebon. Metode penelitian yang digunakan adalah metode kuantitatif dengan metode survei. Teori yang digunakan adalah teori perilaku organisasi dari Stephen P Robbins. Alat pengumpulan datanya adalah angket yang diberikan kepada responden sejumlah 40 guru honorer. Teknik analisis data menggunakan analisis regresi ganda. Hasil penelitian menunjukkan bahwa (1) gambaran tentang kompensasi tinggi (2) gambaran tentang lingkungan kerja kondusif (3) gambaran tentang kinerja guru honorer sedang (4) terdapat pengaruh dari kompensasi dan lingkungan kerja terhadap kinerja guru honorer baik parsial maupun simultan.